Identification of key areas for ecological restoration of territorial space based on ecological security pattern: a case study of Kangbao County - Jiao, Xinying; Tian, Zhipeng; Yang, Huicai; Shang, Guofei; Ma, Jingtao (Frontiers in Ecology and Evolution, 2024)
Accurate identification of key areas for ecological restoration is an important foundation for orderly promotion of ecological restoration of territorial space. This study identified the key areas for ecological restoration in Kangbao County according to the research paradigm of "source identification - resistance surface construction - corridor extraction". First, ecological source sites were identified and screened based on habitat quality modeling, morphological spatial pattern analysis and landscape connectivity analysis. Then, the base resistance surface was constructed using ArcGIS software and nighttime light data. Thereafter, ecological corridors were extracted and ecological pinch points and ecological barrier points identified with the Linkage Mapper plug-in. Forty ecological source sites with a total area of 68.06 km2 were identified in Kangbao County. These sites were dominated by woodland and grassland, and the integrity of these ecological source sites still needed to be improved. The 96 ecological corridors (total length of 743.81 km) were identified, which were densely distributed in the south and east parts of the study area, and there is still much room for improvement of the habitat connectivity. Additionally, 75 ecological pinch points (total area of 31.72 km2) and 69 ecological obstacles (total area of 16.42 km2) were identified. The key areas to be restored were mainly distributed in Yan Yufang, Har Chimega, Tuchengzi, Zhangji, and Danchenghe Townships. This study can lay a firm foundation for the ecological restoration in Kangbao County.